2015
DOI: 10.22226/2410-3535-2015-3-306-312
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure changes in superplastically deformed ultrafine-grained Al-3Mg-0.2Sc alloy

Abstract: Experiments were conducted on an ultrafine-grained Al-3wt.%Mg-0.2wt.%Sc alloy to characterize the microstructure changes occurring during large tensile deformation at elevated temperature within a transition between superplasticity and creep. The coarse-grained material was subjected to equal-channel angular pressing at room temperature using a die which had a 90° angle between the channels. The billets were rotated by 90° in the same sense between each pass in the processing route Bc. The billets were subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The annealed microstructure is quite stable against further static coarsening in short term but the growth of grains occurs during long-term annealing. 26,31) It was observed that the annealing leads to a homogenization of the grain structure but the microstructures with low numbers of ECAP passes remain heterogeneous and contain regions with coarse and fine grains. 32) Furthermore, the annealed microstructure coarsens significantly during subsequent deformation.…”
Section: The Microstructure Of Spd-processed Materialsmentioning
confidence: 99%
“…The annealed microstructure is quite stable against further static coarsening in short term but the growth of grains occurs during long-term annealing. 26,31) It was observed that the annealing leads to a homogenization of the grain structure but the microstructures with low numbers of ECAP passes remain heterogeneous and contain regions with coarse and fine grains. 32) Furthermore, the annealed microstructure coarsens significantly during subsequent deformation.…”
Section: The Microstructure Of Spd-processed Materialsmentioning
confidence: 99%